2022
DOI: 10.1108/tqm-03-2022-0091
|View full text |Cite
|
Sign up to set email alerts
|

The effect of brand experiences and relational benefits on loyalty in the fast-food restaurants

Abstract: PurposeThe aim of this study is to examine the role of relational benefits and brand experience measurements on willingness to pay more (WPM), effects of word of mouth (WOM) and repurchase intention (RI) in fast-food restaurants (FFR).Design/methodology/approachEmploying an online questionnaire survey with a sample size of 503 respondents, the quantitative methodology included multiple regression and factor analysis to facilitate the analyses of data.FindingsRelational benefits and their dimensions (confidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 101 publications
(354 reference statements)
2
8
0
Order By: Relevance
“…The intellectual experience was found to have a higher impact on brand trust than behavioural or sensory experience (Yu and Yuan, 2019). Similarly, Dandis et al (2022a) ascertained that intellectual experiences had a positive impact on outcome relationships in FFRs. Consequently, customers who are cognitively stimulated during their dining experience are more likely to be satisfied, consider such experiences worth visiting again and trust this FFR brand.…”
Section: 22mentioning
confidence: 87%
See 2 more Smart Citations
“…The intellectual experience was found to have a higher impact on brand trust than behavioural or sensory experience (Yu and Yuan, 2019). Similarly, Dandis et al (2022a) ascertained that intellectual experiences had a positive impact on outcome relationships in FFRs. Consequently, customers who are cognitively stimulated during their dining experience are more likely to be satisfied, consider such experiences worth visiting again and trust this FFR brand.…”
Section: 22mentioning
confidence: 87%
“…The behavioural dimension also had a positive impact on brand trust and brand commitment (Jung and Sool, 2012). Similarly, Dandis et al (2022a) found that behavioural experiences had a positive impact on outcome relationships in FFRs. According to Yu and Yuan (2019), behavioural experience may impact trust through attachment, which in turn positively impacts brand trust.…”
Section: 24mentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, Chan et al (2022) stated that interpersonal attraction considerably influenced CCB, which is more prominent when customers believe that the corporate culture is intensely customer-focused. In a nutshell, social benefits resulting from service employees' efforts in the context of services encouraged clients to repeat the purchase, pay more for it, and recommend it to others (Dandis et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The human factor is an essential factor in the success of service organizations. Relational advantages have been proven to favorably influence willingness to pay more, WOM, and repurchase intentions in the context of restaurants (Dandis et al, 2022). A study by Mutsikiwa et al (2020) proved that hotel staff competence significantly and positively impacted customer intention to stay at a hotel.…”
Section: H2: Hotel Stay and Ambiance Has A Significant Positive Effec...mentioning
confidence: 99%